2015
DOI: 10.1007/s13744-015-0338-x
|View full text |Cite
|
Sign up to set email alerts
|

Did Adult Diurnal Activity Influence the Evolution of Wing Morphology in Opoptera Butterflies?

Abstract: The butterfly genus Opoptera includes eight species, three of which have diurnal habits while the others are crepuscular (the usual activity period for members of the tribe Brassolini). Although never measured in the field, it is presumed that diurnal Opoptera species potentially spend more time flying than their crepuscular relatives. If a shift to diurnal habits potentially leads to a higher level of activity and energy expenditure during flight, then selection should operate on increased aerodynamic and ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Diurnal species are less constrained in their time of activity (Freitas et al ., ), and may thus spend more time flying than crepuscular species, and exhibit wing shapes associated with reducing the energy requirements of flight. Penz & Heine () investigated whether diurnal or crepuscular behaviour was reflected in wing morphology across species of Brassolini. Accounting for phylogenetic divergence, they found that wings of diurnal species had a significantly higher AR and lower wing moment of area than wings of crepuscular species, implying that the temporal niche indeed may affect butterfly wing morphology.…”
Section: What Selective Factors Influence Flight and Associated Wing mentioning
confidence: 99%
See 3 more Smart Citations
“…Diurnal species are less constrained in their time of activity (Freitas et al ., ), and may thus spend more time flying than crepuscular species, and exhibit wing shapes associated with reducing the energy requirements of flight. Penz & Heine () investigated whether diurnal or crepuscular behaviour was reflected in wing morphology across species of Brassolini. Accounting for phylogenetic divergence, they found that wings of diurnal species had a significantly higher AR and lower wing moment of area than wings of crepuscular species, implying that the temporal niche indeed may affect butterfly wing morphology.…”
Section: What Selective Factors Influence Flight and Associated Wing mentioning
confidence: 99%
“…Morphological variation is usually studied at the macro‐evolutionary scale using phylogenetic comparative methods: departure from neutral divergence along tree branches implies putative adaptive evolution (e.g. Cespedes, Penz & DeVries, ; Chazot et al ., ; Penz & Heine, ). Within species, comparing morphological divergence with neutral divergence at molecular loci ( F ST / Q ST studies) enables the detection of adaptive micro‐evolution (Koskinen, Haugen & Primmer, ; Leinonen et al ., ; Schäfer et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The parallel modification of wing shape was documented in several different groups of insects and may be acquired by various evolutionary mechanisms (Klingenberg and Gidaszewski 2010 ). Similarity in wing shape may be the effect of adaptation to the specific microhabitat (Chazot et al 2016 ), environmental conditions (Pezzoli et al 1997 ), migration (Suárez-Tovar and Sarmiento 2016 ) or be related with an analogous defense strategy (Barber et al 2015 ) and behavior (Johansson et al 2009 ; Penz and Heine 2016 ). Here we documented, for the first time, that reduction of elytra can affect hind wing evolution and lead to homoplasy in this trait among unrelated insect taxa.…”
Section: Discussionmentioning
confidence: 99%